Morality or ethiticity. An old philosophical dispute - Giusti, Miguel (Estudios de Filosofía, 1992)
The article refers to the Hegelian origin of this dispute, at present being made known because of the existing confrontation between those who attempt to give a rational, normative and universalistic foundation of morality and those defending the legitimacy of traditions and modes of living. The author establishes that it is necessary to situate the discussion in the context of a much more fundamental debate on rationality.